Integration of Canva Based Educational Videos in IPAS Learning to Improve the Learning Motivation of Junior High School Students - Busyra, Nur; Dharmawati, Desak Made (Lembaga KITA, 2025)
This research investigates how the integration of educational videos created with Canva influences learning motivation among junior high school students in IPAS (Ilmu Pengetahuan Alam dan Sosial) classes. The study adopted a quasi-experimental approach, utilizing both pre-test and post-test within control and experimental groups. A total of 60 eighth-grade students from a public junior high school in Jakarta participated, evenly split between the two groups. Over a period of four weeks, students in the experimental group engaged with instructional materials delivered through Canva-based videos, while those in the control group continued with standard classroom methods. To assess learning motivation, a questionnaire grounded in Keller’s ARCS Model—covering Attention, Relevance, Confidence, and Satisfaction—was administered. The instrument comprised 25 items, each rated on a 5-point Likert scale. Data analysis involved both descriptive and inferential statistics, including paired and independent sample t-tests, as well as effect size calculations. Findings indicate a marked improvement in motivation scores among students exposed to Canva-based videos. Specifically, the independent sample t-test produced a value of t = 4.65 with p = 0.000, and Cohen’s d was calculated at 0.86, reflecting a substantial effect. These outcomes point to the potential of visually engaging and interactive video content to boost students’ motivation in IPAS learning environments. The results highlight the practical value of integrating accessible digital tools such as Canva into science and social science teaching, as a means to encourage greater enthusiasm and active participation among students.